Dinamika perubahan tutupan lahan pascabencana likuefaksi 2018 di Kelurahan Petobo, Kota Palu - Tanuda Pedro Rusdiono; Eko Kusratmoko; Tika Nurhasanah; Girlly Marchlina Listyono (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
Land use and land cover change (LULCC) is a key indicator for understanding regional spatial dynamics, particularly in disaster-affected areas. Palu City, which experienced severe liquefaction in 2018, requires detailed land cover change analysis to support disaster-responsive regional development and spatial planning. This study aims to analyze land cover change dynamics in Petobo Sub-district before and after the 2018 liquefaction event using Pleiades imagery and aerial photographs from 2017, 2018, and 2022. A quantitative remote sensing approach was applied, employing automated classification on the Google Earth Engine (GEE) platform using the Random Forest (RF) method, followed by spatial analysis using ArcGIS Pro. The classification results demonstrate high accuracy, with Kappa coefficients of 0.82 in 2017 and 2018, and 0.86 in 2022. The analysis reveals significant land cover changes due to the 2018 liquefaction, particularly a reduction in built-up areas of more than 50%, from 25.03% in 2017 to 12.16% in 2018, before increasing to 15.60% in 2022. The dominance of low vegetation cover, reaching 58.46% in 2022, reflects post-disaster land-use adaptation and policy changes. These findings confirm the effectiveness of remote sensing technologies in supporting post-disaster regional development planning.